Bifunctional Ru‐loaded Porous Organic Polymers with Pyridine Functionality: Recyclable Catalysts for N‐Formylation of Amines with CO2 and H2. Issue 5 (21st January 2021) - Zhang, Kai; Zong, Lingbo; Jia, Xiaofei
Abstract: A series of pyridine functionalized porous organic polymers (POPs‐Py&PPh3 ) have been synthesized by polymerizing tris(4‐vinylphenyl)phosphane and 4‐vinylpyridine. The pyridine moieties in the copolymer materials contribute to CO2 adsorption and promote the subsequent conversion of CO2 . The POP supported Ru catalyst (Ru/POP3 ‐Py&PPh3 ) shows a high catalytic activity (TON up to 710) in the N‐formylation of various primary and secondary amines with CO2 /H2, affording the corresponding formamides in good yields (55–95%) under mild reaction conditions. The heterogeneous catalyst can be easily separated from the reaction system and reused for at least eight cycles in the N‐formylation of morpholine. Abstract :